2021
DOI: 10.11113/aej.v11.16672
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Efficiency of Household Stormwater Detention System

Abstract: This paper describes the evaluation of water storing capacity of a household stormwater detention system based on field data. Collection of field data is often sidelined due to the cost and human capital incurred. However, the true value of field data is demonstrated here by comparing the observed and design data. A field test is completed in a real-life terrace house, utilizing the house’s 95m2 side canopy as roof catchment and 4.40m x 4.70m car porch area to station a detention tank. Precast concrete modular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…The percentage volume of water detained for total rainfall between 11.1 mm to 56.8 mm ranged between 35.2% to 95.6% with a mean value of 73.9%. Comparing this findings to the percentage of volume detained (between 30% to 74%) from the study by Ngu et al [4] for modular pre-cast concrete stormwater detention system; the current subsurface stormwater modules performed slightly better. This could be due to the top soil layer used in the current study that allows runoff to infiltrate and store in the layer before reaching the subsurface modules.…”
Section: On-site Monitoring Of Stormwater Modulessupporting
confidence: 54%
See 1 more Smart Citation
“…The percentage volume of water detained for total rainfall between 11.1 mm to 56.8 mm ranged between 35.2% to 95.6% with a mean value of 73.9%. Comparing this findings to the percentage of volume detained (between 30% to 74%) from the study by Ngu et al [4] for modular pre-cast concrete stormwater detention system; the current subsurface stormwater modules performed slightly better. This could be due to the top soil layer used in the current study that allows runoff to infiltrate and store in the layer before reaching the subsurface modules.…”
Section: On-site Monitoring Of Stormwater Modulessupporting
confidence: 54%
“…In terms of volume attenuation, again, modules with infiltration system performed better than the other two systems with 27% as compared to 19% for loose rock infiltration system and 3.45% for modules storage tank system for 2-year storm [3]. As comparison, a more recent study using modular pre-cast concrete stormwater detention system has shown the effectiveness to detain between 30% to 74% of runoff for total rainfall depth of 42.5 mm to 117.5 mm [4]. One of the factors that determine the water volume that can be detain by the stormwater modules is the porosity/cavity/void ratio of the modules.…”
mentioning
confidence: 99%
“…According to a local study [3] conducted from December 2019 to February 2020 in conjunction with the Northeast Monsoon, it was reported that 90% of the recorded rainfall were below 20 mm, 5% between 20-30 mm, 4% between 30-40 mm and 1% between 40-50 mm. The values of 10-year ARI design storms for 5-, 10-and 15-min are estimated as 23, 36 and 46 mm, as intense rainfalls.…”
Section: Introductionmentioning
confidence: 99%